Arheoloģiskie Atklājumi Kā Izaicinājums Vecās Derības Teoloģijai: Archaeological discoveries as a challenge to the Old Testament Theology. - Rudzītis-Neimanis, Jānis (Cel̜š, 2013)
The purpose of the article is to show the current state of research on the historicity of events mentioned in the Old Testament. For a long time the history of ancient Israel was a more or less critical paraphrase of the Old Testament texts. Nowadays we often face very diverse reconstructions of the history and religion of ancient Israel. This diversity is based on a different view of sources and their classification. The so-called "biblical maximalists" argue that the Old Testament is an accurate record of history and religion of ancient Israel. On the other hand, the "biblical minimalists" argue that the Old Testament is a product created by later generations set in earlier time periods (therefore the Old Testament is minimally useful for reconstructing of history of ancient Israel). They claim that the Old Testament accounts are not interested in historical accuracy because the main function of these texts was to form the identity of Israel as God's people. However, the minimalists' approach to the Old Testament and their methodology how to use and evaluate their sources face several problems. Primary sources from various ancient civilizations also have their own (often propagandistic, selective) perspective. The minimalists' approach can't be justified if it includes only the data from archaeology and ignores the biblical evidence. The authenticity of many archaeological artefacts from illegal excavations or private collections is highly controversial (some of them are forgeries or lack important contextual information). The results of this debate are extended reflection on the methodology and evidence evaluation, and revisiting earlier assumptions, taking with it some lessons, for example, the current debate shows that it's necessary to study ancient Israelite prophecy in its ancient Middle East context, focusing on extra-biblical documentation from the closest countries (e. g., the Tell Deir 'Alla inscription in the case of Bileam (Num 22-24); the example of Bileam indicates that the ancient Israelite prophecy was a part of a wider Middle East phenomenon with some specific features).